Educação, tecnologias e espiritualidade: uma tríade em discussão no âmbito educacional - NASCIMENTO, Clodomir Falcão do (Instituto Federal do Amapá, 2021)
Course Completion Course of the Higher Degree in Computer Science from the Institute of Education, Science and Technology of Amapá for researchers, academics, university students and students in genera l in the area of knowledge of Human Sciences, Technologies and Education in Higher Education courses. It aims to analyze bibliographically in the educational scenario the association between education, technologies and spirituality in the pedagogical con text. Investigate evidence of the interrelationship of spirituality in the educational field. It adopts the method of bibliographic analysis, with a qualitative approach in the field of research in education, technology focused on spirituality in education . It addresses elements of Science and Technology talking about Spirituality in the educational field. It briefly covers the use of technologies in the educational process and pedagogical practices related to the use of technologies in education. It highli ghts the dimension of Spirituality and its articulation with Education and Technologies. It outlines the planning of the bibliographic research procedure, the characterization, the object and the research method. Analytically details the results of the res earch undertaken. It concludes by emphasizing the interdisciplinary pedagogical importance in relation to education, technologies and spirituality aiming to rescue the sense of the multidimensionality of the Integral Being through the renewed and comprehen sive view of the full sense of spirituality to be incorporated into the teaching and learning process.